Pengaruh Karagenan dan Enzim Transglutaminase Terhadap Karakteristik Fisik dan Organoleptik Produk Olahan Daging - Irfan Fadhlurrohman; Amanda Ainan Salsabila; Arga Mandala Putra Ferdiawan; Hafiz Nugraha; Triana Setyawardani; Juni Sumarmono (Universitas Djuanda, 2026)
This study aims to examine the effect of adding carrageenan and the enzyme transglutaminase on the physical and organoleptic characteristics of processed meat products. The method used was a descriptive-qualitative literature review following the PRISMA protocol. Of the 44 articles identified, 21 met the criteria, and 17 key articles were analyzed in depth. The results indicate that carrageenan acts as a gelling agent, water-binding agent, and emulsion stabilizer capable of improving texture, tenderness, and product stability. Meanwhile, the enzyme transglutaminase functions to form cross-links between proteins, thereby improving the compactness, elasticity, and sensory quality of the product. The combination of these two ingredients has proven effective in enhancing the quality of processed meat products, both in terms of physical and organoleptic properties. Selecting the appropriate concentration is a critical factor for achieving optimal product characteristics.